Uji Toksisitas Akut Ekstrak Etanol Sarang Semut (Myrmecodia pendens) Kalimantan pada Mencit (Mus musculus) Swiss - Mart Hindrasyah Pandia, Dhayu; Wibriansyah, Akbar; Pratiwi, Widya; Fajrin Priadinata, Akhmad; Sari, Wening (Lembaga Penelitian Universitas YARSI, 2011)
Sarang semut (Myrmecodia pendans) is an Indonesian native plant that has been used in folk medicine. Researches showed sarang semut has antioxidant effect, Ã‚Â xantinoxidase inhibitor potency, and anticancer activity. The efficacy and safety of this plant should have been proven before used in modern medicine. The objective of this research was to assess the potency of acute toxicity, evaluate toxic clinical symptoms and histopahtologic examination. The research was completly randomized design. The treated animal was 20 Swiss male mice devided into 5 groups; 1 control group with administration of 1% NaCMCÃ‚Â and 4 experimental groups with dosage administration of ethanol extract of sarang semut were 0,1, 1, 10 and 100g/Kg of body weight respectively. Evaluation of the toxic clinical symptoms and death was done in 24 hours and 14 day for survival mice. The test resulted LD50 of ethanol extract of sarang semut was 3,162g/Kg of body weight. All mice in 10 and 100g/kg of body weight groups were death in one hour administration of extract and showed toxic clinical symptom such as hyperactive and convulsion. Histopathologic examination on kidney of the death mice was showed infiltration of inflammation cells and congestive tubules diffuse . The ethanol extract of sarang semut was a slighly toxic substance for Swiss male mice based on Hodge dan Sterner criteria.